2021
DOI: 10.3389/fsoc.2021.610297
|View full text |Cite
|
Sign up to set email alerts
|

The Role Played by Public Universities in Mitigating the Coronavirus Catastrophe in Brazil: Solidarity, Research and Support to Local Governments Facing the Health Crisis

Abstract: This study aims to assess the impacts of the Covid-19 pandemic in Brazil and how it has been dealt with by both the government and in civil society. To this end, we examine the Brazilian public health system and the measures taken by the Bolsonaro Government that led to Brazil being ranked second in overall Covid-19 infections in the world through August 2020. In the absence of national leadership facing the Covid-19 health crisis, we list a set of science-based initiatives promoted by Brazilian public univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Additionally, the right side of Figure 3 shows the descriptive data of performance scores with a 3-point scale (1)(2)(3)(4). Students considered that the university underperformed as a smart campus, since the overall data ranged between 2.23 and 2.86.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the right side of Figure 3 shows the descriptive data of performance scores with a 3-point scale (1)(2)(3)(4). Students considered that the university underperformed as a smart campus, since the overall data ranged between 2.23 and 2.86.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Since scholasticism in medieval European monasteries, universities had become a significant component of societal change, sustainability, and digital transitions [1,2]. They have had a crucial role in recent matters, such as fighting the COVID-19 pandemic, through partnerships and support of governments and civil society [3].…”
Section: Introductionmentioning
confidence: 99%
“…Going forward, (v) volunteer and humanitarian actions by students and academic staff were identified, looking at vulnerable population groups ( Aluisio et al, 2020 ; Arrais et al, 2021 ). It was noted that the pandemic intensified the level of vulnerability of several population groups.…”
Section: Covid-19 and Societal Engagementmentioning
confidence: 99%
“…Furthermore, the review identified (vi) university–government partnerships , mainly formed to conduct research in collaboration with other entities or on demand (in all areas of knowledge). These partnerships included those between universities, governments and communities, as well as joint initiatives aimed at the formulation of public policies, protocols and campaigns, among others ( Arrais et al, 2021 ; Joseph et al, 2021 ; Luppi et al, 2021 ; Maglia and Braida, 2020 ; Maurrasse, 2021 ; Nawangwe, 2021 ; Perrotta, 2021 ; Rosa et al, 2021 ; Souza et al, 2022; Vinson et al, 2021 ). Public–public partnerships have important intersections with other dimensions, especially with (i), (ii) and (vii).…”
Section: Covid-19 and Societal Engagementmentioning
confidence: 99%
See 1 more Smart Citation